Oral Precancer : Diagnosis and Management of Potentially Malignant Disorders. - Thomson, Peter (Wiley-Blackwell, 2012)
Oral Precancer is a preeminent new book that compiles recent research on precancer conditions of the oral cavity and their specific application to the dental field. In addition to providing a scientific and evidence-based survey of the disparate sources of oral precancer research, this book presents practical information for dental practitioners. Written by a prominent researcher in the field, Oral Precancer furnishes its readers with a balanced approach to this highly topical subject.
Includes bibliographical references and index.
Keywords: Mouth -- Cancer; Precancerous Conditions; Mouth -- Cancer; Precancerous conditions; Electronic books; Electronic books